Exploring the impact of parent-child contact, future orientation, and self-esteem on students' learning behavior: A mediation analysis - Jianmin Sun; Mohamed Oubibi; Katsiaryna Hryshayeva (Acta Psychologica)
Introduction: The interaction between parents and children is a crucial determinant of adolescents' learning behavior, future orientation, and self-esteem. Moreover, positive relationships between parents and students significantly enhance these factors, promoting better academic and personal development outcomes. Objective: This study aims to investigate the effects of parent-child contact on learning behavior, with future orientation and self-esteem serving as mediating factors. The research contributes to the existing body of literature by exploring these interconnections. Method: A sample of 1141 students from various schools and academic levels in China participated in the study by completing an online survey. Linear regression analysis was used to examine relationships among the four main variables, and all pathways in the multiple mediation model were tested. Results: The findings revealed that parent-child interaction positively and significantly influences future orientation ((β = 0.490, p < 0.01), self-esteem (β = 0.652, p < 0.01), and learning behavior (β = 0.673, p < 0.01). Conclusion: This research underscores the critical role of parent-child contact, future orientation, and self-esteem in shaping students' learning behavior and their personal and professional development. The results highlight the significant and positive impact of these factors on students' academic outcomes.